2022
DOI: 10.1007/s00018-022-04224-2
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammation and neutrophil extracellular traps in cerebral cavernous malformation

Abstract: Cerebral Cavernous Malformation (CCM) is a brain vascular disease with various neurological symptoms. In this study, we describe the inflammatory profile in CCM and show for the first time the formation of neutrophil extracellular traps (NETs) in rodents and humans with CCM. Through RNA-seq analysis of cerebellum endothelial cells from wild-type mice and mice with an endothelial cell-specific ablation of the Ccm3 gene (Ccm3iECKO), we show that endothelial cells from Ccm3iECKO mice have an increased expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…The results of our in vitro model are also consistent with recently published analyses in Ccm3 iECKO mice. Using an acute, “fast progression” and a chronic, “slow progression” model of CCM, the authors demonstrated that the expression of Ccl2 , Cxcl2 , Cx3cl1 and other immune-related genes was significantly upregulated in brain microvascular ECs of Ccm3 iECKO mice [ 48 ]. In general, the proportion of cells with a Ccm3 deletion is relatively low (< 15%) in the chronic model [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our in vitro model are also consistent with recently published analyses in Ccm3 iECKO mice. Using an acute, “fast progression” and a chronic, “slow progression” model of CCM, the authors demonstrated that the expression of Ccl2 , Cxcl2 , Cx3cl1 and other immune-related genes was significantly upregulated in brain microvascular ECs of Ccm3 iECKO mice [ 48 ]. In general, the proportion of cells with a Ccm3 deletion is relatively low (< 15%) in the chronic model [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using an acute, “fast progression” and a chronic, “slow progression” model of CCM, the authors demonstrated that the expression of Ccl2 , Cxcl2 , Cx3cl1 and other immune-related genes was significantly upregulated in brain microvascular ECs of Ccm3 iECKO mice [ 48 ]. In general, the proportion of cells with a Ccm3 deletion is relatively low (< 15%) in the chronic model [ 48 ]. In the acute model, it is much higher (> 80%) but cells with Ccm3 wild-type alleles are still present [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increase in astrocyte CX3CL1 signaling may play an important role in recruiting both microglia and peripheral inflammatory cells into CCM lesions via the receptor CX3CR1 60 . Moreover, the increase of astrocyte MCP1 ( Ccl2 ), a chemoattractant for monocytes and activated T cells, may synergize with CX3CL1 to recruit the innate and adaptive immune response 58, 61 as well as to induce disassembly of tight junctions in brain endothelial cells during CCM disease 8, 62 . We observed that neuroinflammatory astrocytes induced in CCMs expressed high mRNA levels of CD74, a cell-surface form of the MHC class-II invariant chain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitation of small sample size and the uncertainty of whether the mAbs would react with other antibodies, these data have given us a novel insight into the immunopathogenesis of CCM. In another piece of research, the infiltration of different subsets of leukocytes in CCM was revealed ( 72 ). Through RNA-seq analysis, increased inflammation-related genes were observed in the endothelial cells from CCM mouse model ( 72 ).…”
Section: Immune and Inflammatory Mechanisms For Ccm Formationmentioning
confidence: 99%
“…In another piece of research, the infiltration of different subsets of leukocytes in CCM was revealed ( 72 ). Through RNA-seq analysis, increased inflammation-related genes were observed in the endothelial cells from CCM mouse model ( 72 ). Notably, the cytokines which perform the roles of inflammatory and immune cells’ recruitment, involving proinflammatory cytokines, chemokines, and adhesion molecules, are closely related to the differentially expressed genes.…”
Section: Immune and Inflammatory Mechanisms For Ccm Formationmentioning
confidence: 99%